2016
DOI: 10.1371/journal.pone.0162409
|View full text |Cite
|
Sign up to set email alerts
|

Association of Donor and Recipient Telomere Length with Clinical Outcomes following Lung Transplantation

Abstract: BackgroundPatients with short telomere syndromes and pulmonary fibrosis have increased complications after lung transplant. However, the more general impact of donor and recipient telomere length in lung transplant has not been well characterized.MethodsThis was an observational cohort study of patients who received lung transplant at a single center between January 1st 2012 and January 31st 2015. Relative donor lymphocyte telomere length was measured and classified into long (third tertile) and short (other t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(24 citation statements)
references
References 26 publications
0
20
4
Order By: Relevance
“…In contrast to this study, a previous study by Courtwright and colleagues looked at both donor lymphocyte and recipient lung TL and did not find a significant association with survival in their cohort 7. Another study since then examined recipient TL specifically in patients with pulmonary fibrosis and divided the cohort into two groups of <10th percentile and ≥10th percentile TL and showed significantly worse survival in the <10th percentile even when controlling for other factors such as infection rate, ACR and primary graft dysfunction 8.…”
contrasting
confidence: 92%
“…In contrast to this study, a previous study by Courtwright and colleagues looked at both donor lymphocyte and recipient lung TL and did not find a significant association with survival in their cohort 7. Another study since then examined recipient TL specifically in patients with pulmonary fibrosis and divided the cohort into two groups of <10th percentile and ≥10th percentile TL and showed significantly worse survival in the <10th percentile even when controlling for other factors such as infection rate, ACR and primary graft dysfunction 8.…”
contrasting
confidence: 92%
“…In CLAD, telomere dysfunction is increasingly appreciated as a research target. A small study in lung transplant patients found no association of donor peripheral blood LTL or recipient tissue RTL with survival [ 36 ]. More recently, Faust et al reported that short donor peripheral blood LTL was associated with worse CLAD-free survival after transplantation.…”
Section: Discussionmentioning
confidence: 99%
“…Only one prior study has investigated the effect of telomere length on transplant outcomes(22). This study is similar in that the cohort was stratified by telomere length, and the group with shorter lengths represented ~1/3 of the total.…”
Section: Discussionmentioning
confidence: 99%